Anthropometric comparison of world-calss sprinters and normal populations - Uth, N. (Journal of Sports Science & Medicine, 2005)
The present study compared the anthropometry of sprinters and people belonging to the normal population. The height and body mass (BM) distribution of sprinters (42 men and 44 women) were statistically compared to the distributions of American and Danish normal populations. The main results showed that there was significantly less BM and height variability (measured as standard deviation) among male sprinters than among the normal male population (US and Danish), while female sprinters showed less BM variability than the US and Danish normal female populations. On average the American normal population was shorter than the sprinters. There was no height difference between the sprinters and the Danish normal population. All female groups had similar height variability. Both male and female sprinters had lower body mass index (BMI) than the normal populations. It is likely that there is no single optimal height for sprinters, but instead there is an optimum range that differs for males and females. This range in height appears to exclude people who are very tall or very short in stature. Sprinters are generally lighter in BM than normal populations. Also, the BM variation among sprinters is less than the variation among normal populations. These anthropometric characteristics typical of sprinters might be explained, in part, by the influence the anthropometric characteristics have on relative muscle strength and step length.